Wearing the City: Memory P(a)laces, Smartphones, and the Rhetorical Invention of Embodied Space. Issue 3 (26th May 2016) - Kalin, Jason; Frith, Jordan
Abstract : This article extends research on the production of embodied space by focusing on the relations between place and memory. Beginning with a consideration of how wearable technologies enable new spatial practices within the constructed order of the city, we develop a conceptual framework to understand these spatial practices by returning to the rhetorical art of memory and the building of memory palaces. The art of memory, exemplified by memory palaces, offers a rhetorical resource for understanding how smartphones as wearable technologies may be incorporated—that is, brought into the body, as integral to the production of embodied spatial memories. We argue for the memory-palace builder as an inventive rhetorical (and mobile) figure who not only walks but also wears the city, composing and embedding hybrid memories into and onto hybrid places and, thus, providing a coherent way of being and acting in contemporary urban space.